Hepatocytic expression of human sodium-taurocholate cotransporting polypeptide enables hepatitis B virus infection of macaques - Benjamin J. Burwitz (Nature Portfolio, 2017)
Hepatitis B virus (HBV) has a limited host range and current animal models can only recapitulate certain aspects of HBV replication. Here, the authors show that expression of the HBV receptor NTCP in macaques supports HBV replication in vivo, suggesting this as animal model for future HBV studies.